Kinerja Beberapa Tipe Moisture Meter dalam Penentuan Kadar Air Padi - Fahroji Fahroji; Hendri Hendri (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Fahroji et al, 2016.Â Evaluation of Moisture Meters Performance on Determination of Water Content of Rough Rice. JLSO 5(1):62-70.Moisture content is an important parameter for determining of rice quality. The water content of rough rice affects on milling process because if water content is high, more than 14% of high will result broken rice. The purpose of this research is to study the reliability of moisture meters on determination of the water content of rice grain, accuracy, precision and reproducibility. The sample of measurement are rough rice with 5 different water contents (12%, 14%, 16%, 18% and 20%), while the equipments to be evaluated are the resistance type of moisture meters (Gwon1, Gwon2 and Gwon3), the capacitance type (Kett and Gac), the direct method (type infrared and hot air oven). AOAC method is used as a standard because of its more accurate than the other methods. The result showed that moisture meters performed strong relation with moisture content measured by AOAC as the reference. Kett meter was more accurate than the other moisture meters. All meters showed not satisfied in reliability indicator including accuracy, as well as for Allowed Quality Limit (AQL). Measurement of precision value of resistance type moisture meters indicated high precision and reproducibility from 3 meters are not satisfied.